2013
DOI: 10.1007/s10895-013-1197-7
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Fluorescence Emission Attributes of a Fluorescent dye: 2,3,5,6-Tetracyano-p-Hydroquinone

Abstract: Four cyano groups have been substituted on the aromatic ring of p-hydroquinone (2,3,5,6-tetracyanohydroquinone) in order to study the enhanced photoacidity of this molecule. The acid-base equilibria have been studied using absorption (for ground state pKa) and fluorescence (excited state pKa) spectra. Three distinct species (neutral, anionic and dianionic forms) were observed in the ground state and only two species (anionic and dianionic forms) were found in the excited state when studied at different pH/Ho i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…After the HCl treatment, most of that inorganic matter affecting the titration curve/reacting with the titrant was removed. The shape of the curve for RHC-A in the pH range > 8 suggests that this sample might have a marked contribution of electrochemically active hydroquinones which dissociate between pH 8-10 (0.259 mmol/g) [49]. The results also suggest that on the surface of RHC-B-II 0.280 mmol/g of these groups might be present.…”
Section: Samplementioning
confidence: 82%
“…After the HCl treatment, most of that inorganic matter affecting the titration curve/reacting with the titrant was removed. The shape of the curve for RHC-A in the pH range > 8 suggests that this sample might have a marked contribution of electrochemically active hydroquinones which dissociate between pH 8-10 (0.259 mmol/g) [49]. The results also suggest that on the surface of RHC-B-II 0.280 mmol/g of these groups might be present.…”
Section: Samplementioning
confidence: 82%
“…Therefore, deprotonation of −OH groups easily occurs in the presence of basic reagents (e.g., NaOH and DBU). It is also well known that hydroquinone derivatives can be in a monoanion or dianion form depending on pH. , Zahid et al reported the absorption properties of 2,3,5,6-tetracyano-1,4-hydroquinone (TCHQ) under conditions with various pH using citric acid and Na 2 HPO 4 aqueous solutions. Under pH 2 and 8, absorption peaks attributed to its monoanion and dianion forms were newly observed at 461 and 520 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The use of SHG in collagen, an inherent biomolecular component of tissues, has been a significant development [180] . The ability of SHG and SFG imaging techniques to selectively probe interfaces without being overwhelmed by bulk species is another reason for their application in biology [34,35,40,180] …”
Section: Applicationmentioning
confidence: 99%
“…[12] The wide applications of NLO materials is in SHG, [13,14] telecommunications, [15][16][17] ultrafast pulse measurement, [18] laser frequency conversion, [19] and optical parametric amplification. [20,21] In addition, NLO materials have significant applications in high-resolution imaging, [22] dynamic image processing, [23] sensing, [24][25][26][27] optical data storage, [9,28] quick response, [28][29][30][31][32] optoelectronics, [9,26,28,[33][34][35] industrial processing, [30] signal communication, [26] optical signal processing, [9] real-time target recognition, [28] optical 3D data storage, [31] high NLO productivity, [32] high laser damage threshold, [29,36] and optical frequency conversion. [9] NLO materials are also used in biological imaging, [30,[33][34][35][37][38][39][40]<...…”
Section: Introductionmentioning
confidence: 99%